Analysis of Vulnerability to Transmission of the Covid-19 based on Building Function at Padukuhan Mancasan Kleben, Pandowoharjo, Sleman, Yogyakarta - Afrinia Lisditya Permatasari; Ika Afianita Suherningtyas; Erik Febriarta; Putu Perdana Kusuma Wiguna (Forum Geografi, 2021)
Coronavirus Disease (COVID-19) pandemic is currently being a concern in all parts of the world, including Indonesia. Yogyakarta Special Region, especially Sleman Regency, is a red zone, which is an area that has a very high transmission rate of Covid-19. Padukuhan Mancasan Kleben, is one of the hamlets located near the government center of Sleman Regency where community activity and mobility are quite high. There are many business buildings located along the main road. The purpose of this research is to analyze the vulnerability to transmission of Coronavirus Disease (COVID-19) based on building function using Analytical Hierarchy Process (AHP) and Spatial Multi Criteria Evaluation (SMCE) methods. Types of buildings as houses and store are identified using Unmanned Aerial Vehicle (UAV) image. Types of buildings used as physical variables in the analysis. Based on the result, from total of 363 buildings, there are 35 buildings that have a high level of vulnerability and 328 buildings with low vulnerability. A low level of vulnerability is found in buildings that function as shophouse. Meanwhile, the low level of vulnerability is found in buildings used as houses and public facilities. This is because during the pandemic, several public facilities in Mancasan Kleben are not yet operational. Mitigation efforts that need to be implemented are increasing awareness of ourselves and the surrounding environment. The implementation of healthy living habits by implementing CITA MAS JAJAR, avoiding crowds and not traveling if it is not too important, can help prevent the transmission of Coronavirus Disease (COVID-19)